Mechanism of photoluminescence enhancement and quenching in Nd2O3 nanoparticles–ferroelectric liquid crystal nanocomposites. Issue 20 (6th March 2015) - Goel, Puja; Arora, Manju
<x xml:space="preserve">Abstract</x> The mechanism of photoluminescence enhancement and quenching in np-Nd2O3:FLC nanocomposites has been explored in the current study by UV-Vis and photoluminescence (PL) spectroscopy techniques.